EFFECT OF TELE-VIDEO INSTRUCTION ON DISTANCE LEARNERS’ PERFORMANCE IN EDUCATIONAL TECHNOLOGY - Omoniyi, Tayo (Sokoto Educational Review, 2020)
The study investigated the effect of tele-video instruction on students’ performance in an introductory course in educational technology. It examined the significant difference in the post-test performance scores of students exposed to televideo instruction and their counterparts taught using the conventional method of teaching. The sample consisted of one hundred and sixty distance learners of the Faculty of Education, Olabisi Onabanjo University, Ago-Iwoye, Nigeria. Educational Technology Performance Test (EDTPT), designed by the researcher, was employed to elicit required data and the data collected were analysed using Analysis of Covariance (ANCOVA). The results indicated that the students taught educational technology through exposure to tele-video instruction performed significantly better than those taught using the conventional method of teaching. A significant difference was also reported of the performance of the male and female students, while teaching experience did not significantly influence their performances. Arising from the findings, tele-video was strongly recommended for the delivery of distance learning in Nigeria and other developing countries.